'Equal pay for women - what you should know about it, 1984 (1984)
1984 1960-2000 "'Equal pay for women - what you should know about it, 1984" [EP0040], 1984 This TUC leaflet explains the new amendments to the 1970 Equal Pay Act, in force from 1 January 1984, which introduced the concept of 'equal value'.